Extraction of different temperatures and kinetic freeze-out volume in high energy collisions. (1st September 2022) - Waqas, M; Peng, G X; Ajaz, M; Haj Ismail, A; Wazir, Z; Li, Li-Li
Abstract: We analyze the transverse momentum ( p T ) spectra, 1/ N ev [(1/2 πp T )d 2 N /d y d p T ], of kaon, proton, deuteron and triton in different centrality events in gold–gold (Au–Au) collisions at relativistic heavy ion collisions (RHICs) by Hagedorn thermal model and extracted the excitation function of effective temperature, kinetic freeze-out volume, initial temperature and kinetic freeze-out temperature. We perceived that the effective temperature, initial temperature and kinetic freeze-out temperature sharply increases from 7.7 GeV to 14.5 GeV and then remain static from 14.5–39 GeV, and this consistency may disclose that the onset energy of the phase transition of partial deconfinement and the whole deconfinement are 14.5 and 39 GeV, respectively. The kinetic freeze-out volume and mean transverse momentum grows with the rise of collision energy. Furthermore, the different extracted temperatures are observed in the order of time evolution of the interacting system, and they (as well as kinetic freeze-out volume) have an increasing trend from peripheral to central collisions. We also observed the mass dependence of the effective temperature and kinetic freeze-out volume where former increases while the later decreases for heavier particles, which indicates the early freeze-out of the heavier particles.